2014
DOI: 10.1097/mco.0000000000000108
|View full text |Cite
|
Sign up to set email alerts
|

Fermented food in the context of a healthy diet

Abstract: Although functional foods offer considerable market potential, several issues still need to be addressed. As most of the studies on functional fermented foods are of a rather descriptive and preliminary nature, there is a clear need for mechanistic studies and well controlled in-vivo experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 81 publications
0
23
0
Order By: Relevance
“…The main focus, at the moment, is to prove their functionality, meaning they still have to demonstrate improvements in target functions in the human body leading to health and well-being. Nevertheless, numerous food market options, from milks and yogurts to fermented soy products, cereals, vegetables and juices are already available [20]. Human studies will have to be carried out to validate the potential benefits already shown in in vitro and rats/mice studies up to now.…”
Section: Fermented Foods On Societymentioning
confidence: 99%
“…The main focus, at the moment, is to prove their functionality, meaning they still have to demonstrate improvements in target functions in the human body leading to health and well-being. Nevertheless, numerous food market options, from milks and yogurts to fermented soy products, cereals, vegetables and juices are already available [20]. Human studies will have to be carried out to validate the potential benefits already shown in in vitro and rats/mice studies up to now.…”
Section: Fermented Foods On Societymentioning
confidence: 99%
“…Currently, different kinds of probiotic dairy products are produced and consumed all over the world including pasteurized milk, ice cream, fermented milks, cheese and baby milk powders. Milk and dairy products acquire some nutritional properties like the high lactose content which permit the growth and the existence of probiotic bacteria [17]. Some dairy products likefermented milks and cheesesare also preferred to be a vehicle for probiotic regarding their pH, buffering capacity, and fat content which create an additional protection for probiotics passing gastrointestinal tract and improve their maintenance [39][40][41][42].…”
Section: Dairy Productsmentioning
confidence: 99%
“…Therefore, the matrix and process engineering in food probiotic production are nowadays an advanced and developed science and technology [17][18][19]. However, although production and maintenance of probiotic food products are considerably more difficult than the drug ones, the consumers are expected and enjoy inherently ingesting medicinal additives via food stuffs rather than the drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Most fermented foods contain a variety of microorganisms that might transform chemical constituents of food sources during fermentation, resulting in enrichment of substrates with vitamins, essential amino acids, bioactive compound, improvement of nutrient, inhibition of pathogen, and degrading toxic components (Leroy and De Vuyst 2014;Koo et al 2016). The consumption of fermented food has beneficial effects, including health-promoting, anti-aging, anti-carcinogenic, and anti-obesity activities.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally fermented food and beverages can be classically defined as functional foods with beneficial effects for the host (Stanton et al 2005;Leroy and De Vuyst 2014). Most fermented foods contain a variety of microorganisms that might transform chemical constituents of food sources during fermentation, resulting in enrichment of substrates with vitamins, essential amino acids, bioactive compound, improvement of nutrient, inhibition of pathogen, and degrading toxic components (Leroy and De Vuyst 2014;Koo et al 2016).…”
Section: Introductionmentioning
confidence: 99%